LINGUOPOETIC STUDIES IN THE EXAMPLE OF THE EPIC “RAVSHAN” - Dildora Khudayberganova (Journals Park Publishing, 2023)
In this article, comments were made about the artistry of the “Ravshan” epic, language riches, lexicon. At the same time, the term linguopoetics was briefly touched upon. The main emphasis was placed on the study of lingvopoetics in today’s modern linguistics. Analyzing the language features of this series of epics, attention was paid to their antonyms and their analysis in poetry or prose. The meanings of the antonyms were explained in detail, and their function in the sentence was determined.
Keywords: linguopoetics, antonyms, linguistic units, linguistics, form, text, intertextuality